The application of double elastic band exercise in the 90/90 arm position for overhead athletes - Tsuruike, M.; Ellenbecker, T. S.; Lauffenburger, C. (Sports Health: A Multidisciplinary Approach, 2020)
Background: Traditional exercises performed with the shoulder in the position of 90° abduction and external rotation with elbow flexion (90/90) while using a single elastic band showed moderate activity of both the lower trapezius (LT) and infraspinatus (IS) muscle. The purpose of this study was to investigate activity of the teres minor (TMi) and the LT muscles during standing external rotation exercise with the shoulder in the 90/90 position with 2 elastic bands in both the frontal and the scapular plane.